Implementasi Sistem Informasi Akuntansi Pembayaran Sumbangan Pembinaan Pendidikan Pada Lembaga Pendidikan Tingkat Menengah - Rizka Apriliana; Rifa Nurafifah Syabaniah; Andi Riyanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
SMA Plus Yaspida Sukabumi is an institution engaged in the field of education by combining modern boarding schools and schools. Until now, the process of SPP payment transactions by recording reports into the ledger. The problem that is always faced is the difficulty of finding data which takes quite a long time from the process of searching for data with a large amount of data in the payment data archive. The method of collecting data in this research is by means of observations, interviews and literature studies as well as the development of information systems in making applications using the waterfall method, and the programming language used is PHP, and the MYSQL database. The results of the design of an accounting information system designed to make it easier to search for data in the transaction process and report generation can be done easily and automatically So that the payment transaction process can be carried out effectively and efficiently and can minimize the risk of errors caused by human error.